Parameters for Fabricating Nano-Au Colloids through the Electric Spark Discharge Method with Micro-Electrical Discharge Machining - Tseng, Kuo-Hsiung (Nanomaterials (Basel), 2017)
In this study, the Electric Spark Discharge Method (ESDM) was employed with micro-electrical discharge machining (m-EDM) to create an electric arc that melted two electrodes in deionized water (DW) and fabricated nano-Au colloids through pulse discharges with a controlled on–off duration (T(ON)–T(OFF)) and a total fabrication time of 1 min. A total of six on–off settings were tested under normal experimental conditions and without the addition of any chemical substances. Ultraviolet–visible spectroscopy (UV–Vis), Zetasizer Nano measurements, and scanning electron microscopy–energy dispersive X-ray (SEM–EDX) analyses suggested that the nano-Au colloid fabricated at 10–10 µs (10 µs on, 10 µs off) had higher concentration and suspension stability than products made at other T(ON)–T(OFF) settings. The surface plasmon resonance (SPR) of the colloid was 549 nm on the first day of fabrication and stabilized at 532 nm on the third day. As the T(ON)–T(OFF) period increased, the absorbance (i.e., concentration) of all nano-Au colloids decreased. Absorbance was highest at 10–10 µs. The SPR peaks stabilized at 532 nm across all T(ON)–T(OFF) periods. The Zeta potential at 10–10 µs was −36.6 mV, indicating that no nano-Au agglomeration occurred and that the particles had high suspension stability.